Expression in Escherichia coli of chemically synthesized gene for the human immune interferon. - Tanaka, S (1983)
A 454 base pair fragment of double stranded DNA consisting of a gene for a human immune interferon (hIFN-gamma), initiation and termination signals plus appropriate restriction endonuclease sites, was totally synthesized. The synthesis involved preparation of 62 oligodeoxyribonucleotides by rapid, solid phase procedures, and enzymatic ligation of the oligonucleotides. This synthetic gene was expressed in E. coli under the control of the lac UV5 promoter. The product has antiviral activity which was acid labile and completely neutralized by antiserum to hIFN-gamma but not by antiserum to hIFN-alpha or hIFN-beta. Molecular weight of hIFN-gamma produced by E. coli was estimated to be about 32,000 and 17,000 by gel filtration and SDS-polyacrylamide gel electrophoresis respectively.